Analisis Representasi Nilai Moral dalam Buku Teks Ekonomi SMA - Suherman, Ade; Susanti, Yuyun; Elsyifa, Rachma Rianty (Universitas Galuh, 2025)
This study explores the representation of moral values in senior high school Economics textbooks using a qualitative content analysis approach. The main focus is to identify values such as honesty, responsibility, justice, and social empathy as they appear in both text and illustrations. The textbooks were selected based on their relevance to the Indonesian education curriculum. The findings reveal that although the textbooks contain numerous illustrations related to economic, social, and political activities, moral values are not explicitly presented. Illustrations such as queues at gas stations or the distribution of social aid, which should reflect justice and social responsibility, are given insufficient attention. Economics teachers in Garut also expressed that while the importance of integrating moral values into learning is acknowledged, the available textbooks are still lacking in this regard. The development of more integrated and contextual learning materials is proposed as a solution to strengthen the teaching of moral values in economics education.